Differential effects of mutations in three domains on folding, quaternary structure, and intracellular transport of vesicular stomatitis virus G protein (The Rockefeller University Press, 1988)
The vesicular stomatitis virus glycoprotein (G protein) is an integral membrane protein which assembles into noncovalently associated trimers before transport from the endoplasmic reticulum. In this study we have examined the folding and oligomeric assembly of twelve mutant G proteins with alterations in the cytoplasmic, transmembrane, or ectodomains. Through the use of conformation-specific antibodies, we found that newly synthesized G protein folded into a conformation similar to the mature form within 1-3 min of synthesis and before trimer formation. Mutant proteins not capable of undergoing correct initial folding did not trimerize, were not transported, and were found in large aggregates. They had, as a rule, mutations in the ectodomain, including several with altered glycosylation patterns. In contrast, mutations in the cytoplasmic domain generally had little effect on folding and trimerization. These mutant proteins, whose ectodomains were identical to the wild-type by several assays, were either transported to the cell surface slowly or not at all. We concluded that while correct ectodomain folding and trimer formation are prerequisites for transport, they alone are not sufficient. The results suggest that the cytoplasmic domain of the wild-type protein may facilitate rapid, efficient transport from the ER, which can be easily affected or eliminated by tail mutations that do not detectably affect the ectodomain.